2010
DOI: 10.1051/limn/2010025
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of predation risk and parasitism on the circadian rhythm of foraging activity in the great pond snailLymnaea stagnalis(Gastropoda: Lymnaeidae)

Abstract: -Four experiments were serially carried out conducted to study foraging activity in the freshwater gastropod Lymnaea stagnalis in the absence and presence of predators (crayfish or fish) under daylight and in the dark. The snails were either parasitized by digenean trematodes (Diplostomum pseudospathaceum or Plagiorchis elegans) or remained unparasitized. The snails had an evident circadian foraging rhythm: they preferred diurnal foraging notwithstanding the predators and parasites. However, the snail's parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…If the circadian rhythms of the predator and its prey are different, they might not meet. Previous studies have shown a phenotypic relationship between activity rhythmicity and survival strategies [coyote: Higdon et al, 2019, buffalo: Tambling et al 2015, spider: Jones et al, 2011, snail: Voutilainen, 2010]. Genes involved in circadian rhythms have been reported to affect predator avoidance in squirrels (DeCourcey et al 1997,2000).…”
Section: Introductionmentioning
confidence: 99%
“…If the circadian rhythms of the predator and its prey are different, they might not meet. Previous studies have shown a phenotypic relationship between activity rhythmicity and survival strategies [coyote: Higdon et al, 2019, buffalo: Tambling et al 2015, spider: Jones et al, 2011, snail: Voutilainen, 2010]. Genes involved in circadian rhythms have been reported to affect predator avoidance in squirrels (DeCourcey et al 1997,2000).…”
Section: Introductionmentioning
confidence: 99%